Drivers of litter ingestion by sea turtles: Three decades of empirical data collected in Atlantic Europe and the Mediterranean. (December 2022) - Darmon, Gaëlle; Schulz, Marcus; Matiddi, Marco; Loza, Ana Liria; Tomás, Jesús; Camedda, Andrea; Chaieb, Olfa; El Hili, Hedia A.; Bradai, Mohamed N.; Bray, Laura; Claro, Françoise; Dellinger, Thomas; et al.
Abstract: Sea turtles are considered as bio-indicators for monitoring the efficiency of restoration measures to reduce marine litter impacts on health. However, the lack of extended and standardised empirical data has prevented the accurate analysis of the factors influencing litter ingestion and the relationships with individual health. Historic data collected from 1988 and standard data collected from 2016 were harmonised to enable such analyses on necropsied loggerhead turtles ( Caretta caretta ) in eight Mediterranean and North-East Atlantic countries. Litter was found in 69.24 % of the 1121 individuals, mostly single-use and fishing-related plastics. Spatial location, sex and life history stage explained a minor part of litter ingestion. While no relationships with health could be detected, indicating that all individuals can be integrated as bio-indicators, the mechanistic models published in literature suggest that the high proportion of plastics in the digestive contents (38.77 % per individual) could have long-term repercussions on population dynamics. Highlights: Loggerheads highly impacted whatever the body condition and growth stage. High rate of ingested plastics regarding food augurs long term repercussions. Spatial variations in litter ingestion reflect different risks among areas. All individuals can be considered as indicator for monitoring litter impacts.